Implementation of Global Reporting Initiatives (GRI) Standards in Service Sector Companies - Ririn Breliastiti; Temy Setiawan; Tiwi Herninta; Vivianty; Shelvy (Dinasti Publisher, 2023)
This research is entitled Implementation of Global Reporting Initiatives (GRI) Standards in the Service Sector Companies. Sustainability reporting, aligned with global standards like the GRI Standards, has become imperative for organizations worldwide. This study delves into the application and effectiveness of these standards in diverse sectors, specifically the financial and healthcare industries. Investigating eight companies—four from each sector—this research assesses how GRI Standards guide sustainability reporting practices. The study analyzes the extent of adherence to these standards in disclosing economic, environmental, and social topics. Employing qualitative comparative analysis, Sustainability Reports were meticulously reviewed. Findings unveiled varying degrees of GRI Standards implementation, indicating a need for heightened awareness and training, especially in specific reporting areas. The study recommends investment in training programs for organizations to enhance their grasp and application of GRI Standards. Moreover, collaboration between regulatory bodies and industry associations is vital to formulate sector-specific guidelines, ensuring consistency in sustainability reporting across diverse industries. However, it's crucial to note that the study's scope is limited to the financial and healthcare sectors, warranting further research for a broader understanding of GRI Standards implementation across industries.